Green development of Asia-Pacific cities building better cities towards 2030 - Zhao, Zheng 1979- (New Jersey World Scientific, 2019)
"The book evaluates and analyses the level of green development in over 100 major cities in Asia Pacific. A quantitative analysis of the relationship with economic growth, income distribution, innovation capabilities, service sector, governance levels, and city clusters are accumulated and presented in the form of a new index; the Urban Green Development Index (UGDI). Amongst the cities discussed in the case studies are Penang (Malaysia), Singapore, Vladivostok (Russia), Portland (USA), Hamburg (Germany), and Stockholm (Sweden)"-- Provided by publisher.
Research group of the Asia-Pacific urban green development report -- Background and theoretical interpretation of urban green development -- Basic connotations and analysis framwork of urban green development -- Urban Green Development Index and evaluation index system -- Evaluation results and main research findings of Asia-Pacific urban green development -- Clean technology and sustainable urban solutions in Singapore -- Air governance in London : experiences and strategies -- Urban green energy development in Russia : Vladivostok city -- Green urban development in Asia and the Pacific : water issues for tourism -- Current practice on resource efficiency in Southeast Asian cities -- Case study : Portland urban growth management -- Urban green growth in Japan : the case of Kitakyushu -- Malaysia urban green development : a case study of Penang -- Seoul's experience and inspiration from the governance of Cheonggyecheon -- Taiwan China : a green city underpinned by Youbike -- Inspirations of Hong Kong's severe weather pre-warning and response mechanism for Beijing -- Contributing and creating attractiveness through the development of a sustainable and smart city district : Stockholm Royal Seaport -- Green space and peoples' leisure life : overseas experience and China's reality -- China's regional development strategy and urban green efficiency : based on urban data analysis of the Silk Road economic belt -- Green development strategy of Asia-Pacific cities -- Urban green development strategy in China.
Keywords: Sustainable urban development -- Pacific Area -- Case studies; Sustainable urban development -- Asia -- Case studies; City planning -- Pacific Area -- Case studies; City planning -- Asia -- Case studies